2013
DOI: 10.1007/s12028-013-9931-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Traumatic Encephalopathy: A Critical Appraisal

Abstract: Chronic traumatic encephalopathy (CTE) formerly known as dementia pugilistica is a long-term neurodegenerative disorder associated with repeated subconcussive head injuries in high-contact sports. We reviewed the existing literature on CTE and examined epidemiological trends, risk factors, and its temporal progression, and proposed the underlying pathophysiological mechanisms that may provide unique insights to clinicians with an in-depth understanding of the disease to aid in the diagnosis and prevention, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
0
15
1
Order By: Relevance
“…Case 2 ( E–H ): A 61‐year‐old former professional boxer had a similar degree of CTE ‐related tauopathy ( E , AT 8 immunostain). In fact, both the NFL player and the boxer met neuropathological criteria for CTE stage III tauopathy. However, in contrast to the NFL player, there is marked degeneration within the cerebellum with marked P urkinje cell loss ( F , B ielschowsky silver stain; arrowhead, B asket cell processes without P urkinje cells “empty B askets”).…”
Section: Boxing and American Footballmentioning
confidence: 99%
See 1 more Smart Citation
“…Case 2 ( E–H ): A 61‐year‐old former professional boxer had a similar degree of CTE ‐related tauopathy ( E , AT 8 immunostain). In fact, both the NFL player and the boxer met neuropathological criteria for CTE stage III tauopathy. However, in contrast to the NFL player, there is marked degeneration within the cerebellum with marked P urkinje cell loss ( F , B ielschowsky silver stain; arrowhead, B asket cell processes without P urkinje cells “empty B askets”).…”
Section: Boxing and American Footballmentioning
confidence: 99%
“…However, the ability to diagnose CTE during life is critical to conduct epidemiologic studies on CTE and to eventually plan treatment trials. To address this gap, Montenigro et al proposed new clinical research diagnostic criteria for CTE (61) that overcome the limitations identified (49,58) in the previous criteria (40,43,44,92). The new criteria are based on a systematic review of the previous literature, as well as on the clinical features reported in neuropathologically confirmed cases of CTE without comorbid disease (52,53,86).…”
Section: Clinical Diagnostic Criteriamentioning
confidence: 99%
“…44 The average age of diagnosis for CTE is 54 years old with the youngest case at 18 years old. 45 Young age of disease onset manifests with mood and behavioral disturbances, while older age at time of onset primarily presents with cognitive decline. 46 The latency of onset is variable ranging from a few months to several decades following neurotrauma exposure.…”
Section: Introductionmentioning
confidence: 99%
“…95 Because of the neuropathological similarities with AD and TBI, potential pharmacological and behavioral interventions for these conditions could also be applied to CTE. 74,191 Discussion CTE represents a major public health issue, given the number of athletes and service members who are exposed to concussive and/or subconcussive events. The current state of the science has generated an initial consensus on the neuropathology of CTE.…”
Section: Treatment and Prevention Strategiesmentioning
confidence: 99%